2023
DOI: 10.1017/s0031182023000380
|View full text |Cite
|
Sign up to set email alerts
|

Refugia or reservoir? Feral goats and their role in the maintenance and circulation of benzimidazole-resistant gastrointestinal nematodes on shared pastures

Abstract: Gastrointestinal nematodes threaten the productivity of grazing livestock and anthelmintic resistance has emerged globally. It is broadly understood that wild ruminants living in sympatry with livestock act as a positive source of refugia for anthelmintic-susceptible nematodes. However, they might also act as reservoirs of anthelmintic-resistant nematodes, contributing to the spread of anthelmintic resistance at a regional scale. Here, we sampled managed sheep and cattle together with feral goats within the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Besides the commonly found polymorphisms at codons 167 and 200 (Avramenko et al, 2019; Redman et al, 2015), we detected several mutations at codon 198, occurring in particular with high frequency on the sheep farm in Montagne de l’Oule. In contrast to our study, previous research had found polymorphisms at codon 198, but they were rare (Francis and Šlapeta, 2023; Ramünke et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Besides the commonly found polymorphisms at codons 167 and 200 (Avramenko et al, 2019; Redman et al, 2015), we detected several mutations at codon 198, occurring in particular with high frequency on the sheep farm in Montagne de l’Oule. In contrast to our study, previous research had found polymorphisms at codon 198, but they were rare (Francis and Šlapeta, 2023; Ramünke et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, benzimidazole-resistant nematodes have been detected in free-living populations of roe deer, Capreolus capreolus , living in sympatry with livestock (Chintoan-Uta et al, 2014; Nagy et al, 2017). To date, the role of wild ungulates in the epidemiology of resistant nematodes remains to be determined, but it has been suggested that wildlife may act as a reservoir of resistant nematodes for livestock (Brown et al, 2022; Chintoan-Uta et al, 2014; Francis and Šlapeta, 2023; Laca Megyesi et al, 2019; Walker and Morgan, 2014). However, to accurately evaluate the potential role of wildlife as reservoirs for anthelmintic resistant gastrointestinal nematodes, we need to investigate the presence of resistant nematodes in co-grazing wild and domestic ungulates in different contexts, (i.e., different host species, different landscapes, and under different climatic conditions).…”
Section: Introductionmentioning
confidence: 99%
“…venulosum, O. radiatum, O. columbianum, are among the most widespread gastrointestinal strongylids in domestic and wild small ruminants (Horak & Louw, 1977;Tariq et al, 2010;Mehlhorn, 2016;Halvarsson et al, 2022). Oesophagostomum radiatum and O. venulosum have been found in domestic sheep and wild goats in Australia (Francis & Šlapeta, 2023). Nematodes of the species O. venulosum have been found in moose (Alces alces), red deer (Cervus elaphus) and roe deer (Capreolus capreolus) in the Belarusian Polissia (Shimalov & Shimalov, 2003).…”
Section: Introductionmentioning
confidence: 99%